Reaction of Indonesian Capital Market Investors to the Implementation of Tax Amnesty - Wibowo, Agung; Darmanto, Susetyo (UNIVERSITY OF MERDEKA MALANG, 2017)
This study was an event study that aimed to find empirical evidence of the reaction of Indonesian capital market investors towards the implementation of tax amnesty. The population of this study was consisting of sectoral indexes listed on the Indonesia Stock Exchange during the study period. The data used were secondary data in the form of a daily sectoral index five days before and five days after the event. The statistical test used to test the hypotheses was paired sample t-test. The result showed that there was no significant positive abnormal return in the period around the event date, as well as the period between the pre-event and event date of the tax amnesty implementation. The result also proved that there was no significant difference between the average trading volume activity in the period between pre-event and event date, event date and post event, and pre-event and post event of the tax amnesty implementation. In general, it can be concluded that investors did not respond to the events of the tax amnesty implementation as good news.DOI: https://doi.org/10.26905/jkdp.v21i4.1607